Adenocarcinoma of the duodenum arising from Brunner’s gland resected by partial duodenectomy: a case report - Tetsuya Mochizuki; Nobuaki Fujikuni; Koichi Nakadoi; Masahiro Nakahara; Kazuaki Tanabe; Shuji Yonehara; Toshio Noriyuki (Surgical Case Reports)
Abstract Background Duodenal carcinoma originating in Brunner’s gland is rare. Herein, we report a case of duodenal carcinoma arising from Brunner’s gland in a 63-year-old man. Case presentation On diagnostic imaging, the lesion presented as a non-invasive carcinoma; the patient also had uncontrolled diabetes and liver cirrhosis. Hence, we decided to perform partial duodenectomy to reduce operative stress. Pathological examination revealed that the tumor consisted of tissue from Brunner’s gland. Additionally, the carcinoma cells were strongly positive for Mucin-6 protein, which is an epithelial marker of Brunner’s gland. The patient’s post-operative course was uneventful, and he has been well for 2 years after the surgery. Conclusions This a rare case of an adenocarcinoma arising from Brunner’s gland of the duodenum that was resected by duodenectomy.